Technology and its interventional value in patient-reported outcomes in cancer research, what is next? - Mendoza, Luis (International Journal of Clinical Trials, 2022)
For cancer patients, health-related quality of life (QOL) is a critical aspect of care management decision-making. In some cases, clinicians have even prioritized QOL over survival in patients with advanced cancer. Over time, patient-reported outcomes (PRO) have gained prominence in cancer research to capture aspects of a patient's health condition, reported directly by the patient through a questionnaire through scales validated in different moments. PROs are currently used as a research tool in clinical trials for cancer drug development to monitor and assess the psychological and cognitive well-being of patients and detect significant symptoms. In addition to QOL, several studies have suggested that PROs also improve patient outcomes and satisfaction. Retrospective analyses have shown that QOL and its early palliative care are a prognostic factor for survival in cancer patients. Although, such results were not confirmed by others who have reported after a systematic review of 24 controlled trials a limited statistically significant impact of PRO, and that the effect sizes of interventional PROs were small to moderate.